2008
DOI: 10.1128/iai.00618-08
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli CFT073 Is Adapted to Acetatogenic Growth but Does Not Require Acetate during Murine Urinary Tract Infection

Abstract: In vivo accumulation of D-serine by Escherichia coli CFT073 leads to elevated expression of PAP fimbriae and hemolysin by an unknown mechanism. Loss of D-serine catabolism by CFT073 leads to a competitive advantage during murine urinary tract infection (UTI), but loss of both D-and L-serine catabolism results in attenuation. Serine is the first amino acid to be consumed in closed tryptone broth cultures and precedes the production of acetyl phosphate, a high-energy molecule involved in intracellular signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…Acetyl phosphate also regulates the biosynthesis of some virulence factors such as pili and capsule (Wolfe et al, 2003;Wolfe, 2005), and plays a role in the pathogenesis of some bacteria. A pta mutant of the urinary E. coli CFT073 showed the inability to colonize the mouse kidney (Anfora et al, 2008). In Salmonella enterica Typhimurium a pta mutant was shown to be impaired in growth and attenuated in BALB/c mice (Kim et al, 2006).…”
Section: Proteomic Analysis Of Stec M03mentioning
confidence: 99%
“…Acetyl phosphate also regulates the biosynthesis of some virulence factors such as pili and capsule (Wolfe et al, 2003;Wolfe, 2005), and plays a role in the pathogenesis of some bacteria. A pta mutant of the urinary E. coli CFT073 showed the inability to colonize the mouse kidney (Anfora et al, 2008). In Salmonella enterica Typhimurium a pta mutant was shown to be impaired in growth and attenuated in BALB/c mice (Kim et al, 2006).…”
Section: Proteomic Analysis Of Stec M03mentioning
confidence: 99%
“…Our knowledge of Pta and its physiological role has largely been limited to bacterial enzymes. The Pta-Ack pathway has been shown to be essential for growth and invasion in several pathogenic bacteria, including Vibrio cholerae (46), uropathogenic E. coli (47), S. enterica (48), and Listeria monocytogenes (49). A eukaryotic Pta has not previously been characterized, and the only report on the physiological role of a nonbacterial Pta is from the green alga Chlamydomonas (19).…”
Section: Discussionmentioning
confidence: 99%
“…Human urine also contains D-serine at concentrations between 3 and 115 mg/mL [40], which is toxic to some nonuropathogens but can be utilized or detoxified by uropathogenic E. coli CFT073. Welch and coworkers demonstrated that D-serine is preferentially consumed in tryptone broth by uropathogenic E. coli CFT073, and that the genes associated with acetate metabolism, including ackA and pta are upregulated, but acs is downregulated, following exposure to D-serine, which is catabolized into ammonia and pyruvate by serine deaminases [16]. Finally, the authors proposed that acetyl~P and acetyl-CoA whose intracellular levels are maintained by Pta and AckA play role in colonization of the urinary tract by CFT073 [16].…”
Section: Allosteric Inhibition Of S Saprophyticus Pta Activity By α-mentioning
confidence: 99%
“…Welch and coworkers demonstrated that D-serine is preferentially consumed in tryptone broth by uropathogenic E. coli CFT073, and that the genes associated with acetate metabolism, including ackA and pta are upregulated, but acs is downregulated, following exposure to D-serine, which is catabolized into ammonia and pyruvate by serine deaminases [16]. Finally, the authors proposed that acetyl~P and acetyl-CoA whose intracellular levels are maintained by Pta and AckA play role in colonization of the urinary tract by CFT073 [16]. Sakinc et al showed that S. saprophyticus, but not the other Staphylococcus species that do not possess D-serine deaminase, tolerates a high concentration of D-serine [41].…”
Section: Allosteric Inhibition Of S Saprophyticus Pta Activity By α-mentioning
confidence: 99%
See 1 more Smart Citation